PREDICTABILITY AND IRREVERSIBILITY OF GENETIC CHANGES ASSOCIATED WITH FLOWER COLOR EVOLUTION IN PENSTEMON BARBATUS - Wessinger, Carolyn A.; Rausher, Mark D. (Evolution, 2014)
Two outstanding questions in evolutionary biology are whether, and how often, the genetic basis of phenotypic evolution is predictable; and whether genetic change constrains evolutionary reversibility. We address these questions by studying the genetic basis of red flower color in Penstemon barbatus. The production of red flowers often involves the inactivation of one or both of two anthocyanin pathway genes, Flavonoid 3′,5′-hydroxylase (F3′5′h) and Flavonoid 3′-hydroxylase (F3′h). We used gene expression and enzyme function assays to determine that redundant inactivating mutations to F3′5′h underlie the evolution of red flowers in P. barbatus. Comparison of our results to previously characterized shifts from blue to red flowers suggests that the genetic change associated with the evolution of red flowers is predictable: when it involves elimination of F3′5′H activity, functional inactivation or deletion of this gene tends to occur; however, when it involves elimination of F3′H activity, tissue-specific regulatory substitutions occur and the gene is not functionally inactivated. This pattern is consistent with emerging data from physiological experiments indicating that F3′h may have pleiotropic effects and is thus subject to purifying selection. The multiple, redundant inactivating mutations to F3′5′h suggest that reversal to blue-purple flowers in this group would be unlikely.